Prostaglandin d synthase is a potential novel therapeutic agent for the treatment of gastric carcinomas expressing PPARγ. Issue 5 (8th January 2015) - Fukuoka, Tatsunari; Yashiro, Masakazu; Kinoshita, Haruhito; Morisaki, Tamami; Hasegawa, Tsuyoshi; Hirakawa, Toshiki; Aomatsu, Naoki; Takeda, Hiroshi; Maruyama, Takayuki; Hirakawa, Kosei
<x xml:space="preserve">Abstract</x> The antitumor activity of prostaglandin (PG) D2 has been demonstrated against some types of cancer, including gastric cancer. However, exogenous PGD2 is not useful from a clinical point of view because it is rapidly metabolized in vivo. The aim of this study was to clarify the antitumor efficacy of an alternative, PGD synthase (PGDS), on gastric cancer cells. The effects of PGD2 and PGDS on the proliferation of gastric cancer cells were examined in vivo and in vitro. The expression levels of PGD2 receptors and peroxisome proliferator‐activated receptor γ (PPARγ) were evaluated by RT‐PCR. The effects of a PPARγ antagonist or siPPARγ on the proliferation of cancer cells and the c‐myc and cyclin D1 expression were examined in the presence or absence of PGD2 or PGDS. PPARγ was expressed in gastric cancer cell lines, but PGD2 receptors were not. PGD2 and PGDS significantly decreased the proliferation of gastric cancer cells that highly expressed PPARγ. PGDS increased the PGD2 production of gastric cancer cells. A PPARγ antagonist and siPPARγ transfection significantly suppressed the growth‐inhibitory effects of PGD2 and PGDS. Expression of c‐myc and cyclin D1 was significantly decreased by PGD2; this inhibitory effect was suppressed by PPARγ antagonist. Both PGD2 and PGDS significantly decreased subcutaneous tumor growth in vivo. Tumor volume after PGDS treatment was significantly less than PGD2 treatment. These findings suggest that PGDS and PGD2 decrease the proliferation of gastric cancer cells through PPARγ signaling. PGDS is a potentially promising therapeutic agent for gastric cancers that express PPARγ.